A population-based study of cervical cytology findings and human papillomavirus infection in a suburban area of Thailand - Natacha Phoolcharoen; Nuttavut Kantathavorn; Thaniya Sricharunrat; Siriporn Saeloo; Waraphorn Krongthong (Elsevier, 2017)
Despite the high incidence of cervical cancer in Thailand, large population-based studies on cervical cytology and HPV prevalence and genotype distribution are rare. This study aimed to determine cervical cytology results and the prevalence and distribution of HPV among Thai females in Bangkhayaeng subdistrict, Pathumthani province, Thailand. Of 4681 female inhabitants, aged 20-70 years, 1523 women finally participated in the study. Cervical samples using liquid-based cytology were collected during February-August 2013 and analyzed for HPV genotype by the LINEAR ARRAY® HPV Genotyping Test (Roche, USA). All participants with abnormal cytology or HPV positivity underwent colposcopy and biopsy. Of 1523 eligible women, 4.1% had abnormal cytology including ASC-US (2.4%), LSIL (1.0%), and HSIL (0.5%). The HPV infection rate was 13.7%. The prevalences of high-risk, probable high-risk, and low-risk HPV types were 5.6%, 3.5%, and 6.8%, respectively. The most common high-risk HPV types detected were HPV-16 (1.31%), HPV-51 (1.25%), and HPV-52 (1.25%). The most common probable high-risk and low-risk HPV types detected were HPV-72 (1.51%), HPV-62 (1.38%), and HPV-70 (1.18%). The rates of CIN2-3 and cancer in this cohort were 1.4% and 0.3%, respectively. In conclusion, HPV prevalence in this study was lower than reported in studies conducted in Western countries or other Asia countries, despite the high prevalence of CIN2+ and cancer. HPV type screening results of the general population in Bangkhayaeng subdistrict were similar to those reported in other countries, with HPV-16 the most common type. However, higher frequencies of HPV-51 and HPV-52 were observed. Despite the availability of a free screening program in this area, the participation rate remains low.